High-clearance anti-amyloid immunotherapies in Alzheimer's disease. Part 1: Meta-analysis and review of efficacy and safety data, and medico-economical aspects - Villain, N.; Planche, V.; Levy, R. (Revue neurologique, 2022)
In 2021, aducanumab, an immunotherapy targeting amyloid-β, was approved for Alzheimer's disease (AD) by the US Food and Drug Administration thanks to positive results on a putative biological surrogate marker. This approval has raised an unprecedented controversy. It was followed by a refusal of the European Medicine Agency, which does not allow the marketing of drugs solely on biological arguments and raised safety issues, and important US coverage limitations by the Centers for Medicare & Medicaid Services. Two other anti-amyloid immunotherapies showed significant results regarding a clinical outcome in phase 2 trials, and five drugs are being studied in phase 3 trials. Compared to those tested in previous trials of the 2010s, the common feature and novelty of these anti-amyloid immunotherapies is their ability to induce a high clearance of amyloid load, as measured with positron emission tomography, in the brain of early-stage biomarker-proven AD patients. Here, we review the available evidence regarding efficacy and safety data and medico-economical aspects for high-clearance anti-amyloid immunotherapies. We also perform frequentist and Bayesian meta-analyses of the clinical efficacy and safety of the highest dose groups from the two aducanumab phase 3 trials and the donanemab and lecanemab phase 2 trials. When pooled together, the data from high-clearance anti-amyloid immunotherapies trials confirm a statistically significant clinical effect of these drugs on cognitive decline after 18 months (difference in cognitive decline measured with CDR-SB after 18 months between the high dose immunotherapy groups vs. placebo = −0.24 points; P=0.04, frequentist random-effect model), with results on ADAS-Cog being the most statistically robust. However, this effect remains below the previously established minimal clinically relevant values. In parallel, the drugs significantly increased the occurrence of amyloid-related imaging abnormalities-edema (ARIA-E: risk ratio=13.39; P<0.0001), ARIA-hemorrhage (risk ratio=2.78; P=0.0002), and symptomatic and serious ARIA (7/1321=0.53% in the high dose groups versus 0/1446 in the placebo groups; risk ratio=6.44; P=0.04). The risk/benefit ratio of high-clearance immunotherapies in early AD is so far questionable after 18 months. Identifying subgroups of better responders, the perspective of combination therapies, and a longer follow-up may help improve their clinical relevance. Finally, the preliminary evidence from medico-economical analyses seems to indicate that the current cost of aducanumab in the US is not in reasonable alignment with its clinical benefits.